Chlorotrimethylsilane and Sodium Iodide: An Expedient Combination for the Chemo/Regioselective Dehalogenation of Benzothiazole and Thiazole Derivatives. Issue 3 (18th January 2023) - Vetrichelvan, Muthalagu; Sankar, Ulaganathan; Bokkala, Vijayabhaskar; Akunuri, Arun; Ramesh, Natesan; Pitchai, Manivel; Mathur, Arvind; Gupta, Anuradha
Abstract: The combination of chlorotrimethylsilane and NaI is disclosed as a reducing system for protodehalogenation of benzothiazole and thiazole derivatives; surprisingly, the alkoxy groups present in the system are unaffected. The optimized reaction conditions tolerate various functional groups and display good efficiency in the regioselective protodehalogenation of a variety of benzothiazole and thiazole derivatives. In addition, the potential application of the protocol was examined by comparing it with previously developed methods; in most of the cases, the present strategy resulted in better yields under milder condition. The mechanistic studies suggest that the reaction probably proceeds through a radical pathway. Abstract : The combination of chlorotrimethylsilane and sodium iodide was disclosed for the chemoselective as well as regioselective protodehalogenation of benzothiazole and thiazole derivatives. Unpredictably, the alkoxy groups present in the system are unaffected and, demonstrated in a large‐scale synthesis.